Changes in drugs´ preferences due to the introduction of new generic medicines - Figueira, Joana Maria Fernandes Alves Toscano (2020)
The purchase of generic drugs has been increasingly encouraged by Governments, as a way of reducing health costs. However, their acceptance by consumers is not that straightforward and it has been seen some resistance associated with lack of information and some other factors, including loyalty to previously used branded products. Thus, this dissertation aims to study the consumers’ preferences over generic drugs, by clarifying some of these speculations while trying to check whether the data confirms these reasonings. This was possible by exploring a rich database from the Portuguese National Association of Pharmacies, which includes very detailed information of each medicine sales at pharmacies in Portugal. The results show that when introducing one more equivalent generic medicine in a group, the individual share of each drug decreases, although the generic ones suffer a higher decrease in their shares. Additionally, generic drugs tend to have a lower individual share than the equivalent branded medicines. Afterwards, over a short time, even on year-on-year comparisons, the shares of generic drugs tend to increase, opposed to the shares of branded products, which indicates a relatively fast change in preferences, based on the speed of information spreading and reputation building. Although in the analyzed sample people buy more generic than non-generic drugs, it is shown that if one more generic medicine and the correspondent proportion of branded drugs is introduced such that the proportion of equivalent generic drugs remains unchanged, the branded products will immediately capture a higher market share.